A Cross Sectional Study to assess Beliefs, Behaviours, and Opinions about Blood Donation among visitors of admitted patients at tertiary Care Hospital, Ahmedabad - Patel, Himadri; Prajapati, Arpit; Modi, Madhur; Chaudhari, Sahilkumari (Indian Journal of Community Health, 2024)
Background: A significant number of patients admitted to hospitals in low- and middle-income countries face the challenge of not having timely access to a safe and free blood supply and India is no exemption. Aims & Objectives: To assess beliefs, behaviours and the exploration of barriers about Blood Donation among visitors of admitted patients. Methodology: A cross section study was done among 356 visitors of admitted patients of tertiary care hospital of Ahmedabad city. Visitors were selected through non probability sampling technique from wards of hospital. Results: Average age was 39.1 ± 11.2 years and 53.9% were male. Only 21.3% people had done blood donation in the past ever. Male were significantly donated the blood (p<0.0001). 94.9% people found blood donation as an important act and 98.3% believed that it can save lives. 39.9% and 12.9% had a knowledge regarding minimum eligible age and weight for blood donor respectively. Donating blood would lead to weakness (37.8%), vertigo (13.3%), infection and HIV (17.8%). Conclusion: People may find blood donation as a significant step to prevent many deaths but very few of them had done blood donation in past ever. People are having fear and misconceptions that is preventing them from donating blood.